JENIS TINDAK TUTUR YANG MENGIKUTI INTERJEKSI PANGGILAN DALAM BAHASA JEPANG - Maharani Patria Ratna (IZUMI, 2015)
[Types of Speech Acts Following Calling Interjection In Japanese] In speaking, there are times when a calling interjection can be followed by more than one type of speech acts. This research discusses the calling interjection which are used by male speakers in the film Brother Beat. In addition, this study also discussed what kind of speech acts that may follow the call in a speech interjection. The data in this study is a narrative that contains interjection calling spoken by male speakers in the Brother Beat movie. The method used is descriptive qualitative method. To get the data, the researcher usesscrutinize technique and tapping notes method. The results obtained in this research are, calling interjection, such as Anosa, oi, Anona, nee, you, and ano, are often used by male speakers to call the addressees. After the calling interjection, directive speech act and assertive speech act are speech act which appear to follow the calling interjection. Interjection ano sa, oi, anona, and ano, are types of calling interjection which can be followed by a directive speech acts and assertive speech act. In the other hand, calling interjection of nee, can be only  followed by a directive speech act, while calling interjection of you can be followed by a ssertives speech act.